Development of Pisa-Like Mathematical Problems on The Change and Relationship Content to Measure the Mathematical Solution Ability of Middle School Students - Wahida Amalia, Mulyono, E. Elvis Napitupulu (International Journal of Advanced Science and Technology, 2020)
This study aims to: produce PISA-LIKE math questions on valid and practical Change and Relationship content to measure the mathematical problem solving ability of junior high school students. This research is a research and development type of formative evaluation Tessmer which consists of two stages namely; (1) preliminary stage, and (2) formative evaluation stage which includes self-evaluation and prototyping. The prototyping stage consists of expert reviews, one-to-one, small groups, and field tests. The subjects of this study were students of grade IX-I junior high school Dr. Wahidin Sudirohusodo, amounting to 36 students. The results showed that the PISA-LIKE math problem has been developed on quality Change and Relationship content from the validity and practical aspects. Validation is based on the results of validation by experts who state "the problem can be used with a little revision", with a reliability coefficient of 0.835 (very high reliability). Practical based on expert judgment, teacher response questionnaire and student response questionnaire. The results of the teacher’s questionnaire response of 83.33% were "very positive" to the questions that had been given, while the students’ response of 75% was "positive" to the questions that had been given by researchers. Based on the results of data analysis students’ mathematical problem solving abilities obtained an average score of 44.25. This value indicates that the level of students’ mathematical problem solving ability is included in the "medium" category.